Serum levels of soluble IL-2R, CD4 and CD8 in bronChial asthma - G. Di Lorenzo; P. Mansueto; M. Melluso; G. Morici; F. Norrito; D. Cigna; G. Candore; C. Caruso (Mediators of Inflammation)
The aim of the present study was to compare serum levels of soluble forms of interleukin-2 receptor, CD4 and CD8, released by lymphocytes during activation of the immune system, in patients with allergic bronchial asthma, with those in healthy subjects. Significantly higher levels of soluble IL-2R and soluble CD4 were found in patients with asthma compared with the control group. In contrast, lower levels of soluble CD8 values were found in patients with asthma compared to the control group. Significant correlations were found for both sIL-2R and sCD4 and these two molecules, with lung function measured as bronchial responsiveness to inhaled methacholine. These results strengthen previous suggestions that in allergic bronchial asthma, activation of T cells plays a significant role in the disease pathogenesis.